APPROPRIATE EMPIRICAL ANTIBACTERIAL THERAPY FOR SEVERE INFECTIONS WITH NON-FERMENTERS - Laura Ghibu; Egidia Miftode; Olivia Dorneanu; Codrina Bejan; Andra Teodor; Cătălina Luca; Carmen Dorobăţ (Romanian Journal of Oral Rehabilitation, 2014)
The outcome of patient with severe infection depends on time of initiation of right antimicrobial therapy. Aim: The emergence of antimicrobial resistance and the severity of nosocomial infections determined by nonfermenters prompted our interest to study the overall antimicrobial resistance profile of Gram negative nonfermenters in order to determine the appropriate empirical antibacterial therapy. Material and methods: In our study were included 85 Pseudomonas aeruginosa strains and 39 Acinetobacter baumannii strains isolated from patients admitted in the Clinic of Infectious Diseases of Iasi from 2006 to 2011. These strains were tested to beta-lactams, fluoroquinolones, aminoglycosides and colistin. Results: Pseudomonas aeruginosa strains showed resistance to ceftazidime (55.6%), cefoperazone (64.6%), ciprofloxacin (87.5%), amikacin (55.6%), imipenem (53%) and to colistin in 2 % of cases. Acinetobacter baumannii strains were resistant to ceftazidime (80%), cefoperazone (87.5%), ciprofloxacin (76.9%), amikacin (45.5%), piperacillin - tazobactam (64.7%), imipenem (44.1%) and colistin in 38.9% of cases. Conclusions: If an infection with Pseudomonas aeruginosa is suspected, the choice of imipenem in starting treatment may be conducive to treatment failure in almost half of cases. Colistin is an effective alternative, but encumbered by renal toxicity. For infections with Acinetobacter baumannii remains the same risk of treatment failure if imipenem therapy is the first intention. More than one third of the cases treated with colistin may result also in failure.